IMPLEMENTASI (P5) PROYEK PENGUATAN PROFIL PELAJAR PANCASILA KARAKTER GOYONG ROYONG DI KELAS 4 SDN KETAPANG - Fitria Rosmi; Apriliyah, Mega (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation process of the Pancasila Student Profile Strengthening Project (P5) with a focus on the value of mutual cooperation in the fourth grade of SDN Ketapang, as well as to identify the obstacles and impacts on students’ character development. This research is motivated by the need to instill Pancasila values, particularly the spirit of togetherness, tolerance, and collaboration, amid the increasing individualism in the learning environment. This study employs a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation. The research subjects consist of the principal, fourth-grade teacher, and students of SDN Ketapang. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of P5 is carried out in a structured manner through planning, implementation, and evaluation stages, involving various collaborative activities such as community service, class bulletin board creation, green garden projects, student discussions, and anti-bullying projects. Teachers act as facilitators, while students actively participate as the main actors in the learning process. The main obstacles identified include limited parental involvement, time constraints in academic schedules, and the need for further teacher training. Nevertheless, the project has successfully improved students’ social awareness, responsibility, communication skills, and cooperation. The implementation of P5 has proven effective in strengthening the value of mutual cooperation and in creating an inclusive and collaborative school environment.